Pharmacognostic, Phytochemical and Antimicrobial Study of Vidangadi Churna - An Experimental Study - Chhaju Ram Yadav; Chudasama Hardik Y (AYUSHDHARA, 2024)
Herbal medicines are gaining more and more attention all over the world as they have been in use since ancient times and have no side effects if taken under proper supervision. But they have their own limitations as data about standardization and quality control are not widely available. Therefore, it is the need of the hour to revalidate this herbal compound under the lens of advance tools or procedures. Method: Vidangadi Churna was prepared according to the classical reference. Physiochemical and Phytochemical study was performed by proper WHO guidelines and Antimicrobial activity of Vidangadi Churna was tested by Agar well diffusion method. Result and Discussion: In this study Vidangadi Churna showed the presence of phytochemical constituents having antimicrobial properties. This preparation was treated with different reagents and examined under UV light. Different reagents showed different colours of the preparation at different wavelengths. Various physiological active compounds like phenolic compounds, Tannins, Amino acids, alkaloids etc. were found in Vidangadi Churna. Antimicrobial study revealed the activity of this drug on different micro-organisms. Conclusion: Vidangadi Churna is poly-herbal Ayurveda formulation described in Yogratnakar in Kustha Roga Chikitsa Adhyay. By this study it is concluded that Vidangadi churna fulfilled all the standard criteria with effective parameters and it could be used as anti-microbial agent against infections caused by Klebsiella aerogenes, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus.